2019
DOI: 10.5507/bp.2018.077
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of abdominal aortic aneurysm in patients with inguinal hernia

Abstract: Aims. There is increased prevalence of inguinal hernia (ΙΗ) in patients with abdominal aortic aneurysm (AAA). As there is limited data on AAA in patients with ΙΗ our objective was to examine the prevalence of AAA in such patients. Methods. We prospectively examined 185 consecutive patients for AAA who presented to our department for surgical repair of an ΙΗ. All patients were referred for ultrasound of the abdominal aorta. An AAA was considered to be present when the distal diameter of the abdominal aorta was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…A recent study investigated the prevalence of AAA in patients with inguinal hernias and demonstrated a 27.7% prevalence of AAA among the study group. 22 The prevalence of incisional hernias has been reported in 19 studies, 12 of which presented a comparison between AAA and control groups (►Table 2). Only 7 of 12 studies found a significant difference in the prevalence of incisional hernias between AAA (range: 10-37%) and control (range: 3-26%) groups (►Table 2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study investigated the prevalence of AAA in patients with inguinal hernias and demonstrated a 27.7% prevalence of AAA among the study group. 22 The prevalence of incisional hernias has been reported in 19 studies, 12 of which presented a comparison between AAA and control groups (►Table 2). Only 7 of 12 studies found a significant difference in the prevalence of incisional hernias between AAA (range: 10-37%) and control (range: 3-26%) groups (►Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study investigated the prevalence of AAA in patients with inguinal hernias and demonstrated a 27.7% prevalence of AAA among the study group. 22 …”
Section: Discussionmentioning
confidence: 99%